The Influence of Strategic Management Accounting and Tax Awareness on Tax Compliance with Moderating Variables of Organizational Performance - Hutagalung, Dhaniel (International Journal of Social Science and Business, 2024)
This study analyzes the influence of Strategic Management Accounting and Tax Awareness on Tax Compliance, with Organizational Performance as a moderating variable, in the context of MSMEs in Banten, West Java, and Jakarta. Using a quantitative method with PLS-SEM, this study processed data from 392 respondents. This research method uses a quantitative approach with a survey method through a questionnaire, which was distributed to Micro, Small, and Medium Enterprises (MSMEs) in Banten, West Java and Jakarta. The sample used was 392 MSMEs, and the data obtained were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationship between variables and the moderating role of organizational performance. The results of the study indicate that Strategic Management Accounting and Tax Awareness have a positive effect on Tax Compliance, but Organizational Performance does not strengthen the relationship, even weakens the relationship between Tax Awareness and Tax Compliance. The study includes differences in business characteristics, dependence on primary data, and model complexity. Therefore, further research with more homogeneous samples and more varied measurement methods is needed. In practice, this study highlights the importance of tax education, increasing understanding of tax regulations, and digitalizing the tax system in improving MSME compliance. The main contribution of this study is the development of Tax Awareness measurement with three new dimensions that support Tax Compliance in the MSME sector.